Characterization of cell phone use while driving in Jordan - Ismeik, Muhannad; Al-Kaisy, Ahmed (Transport, 2010)
A substantial body of research has shown that the use of cell phones while driving can impair driving performance thus representing a relevant traffic safety issue. The conducted studies have indicated that with an increase in general cell phone use, phoning while driving has also grown. For around 80% of Jordan's population that own cell phones, phoning while driving has become a legitimate concern for potential safety hazards. In order to effectively target interventions towards the drivers using cell phones while driving, information about the characteristics of these respondents is needed. The present study investigates the extent of cell phone use on Jordan's roads and the characteristics of drivers who use cell phones while driving. The data was collected using a questionnaire survey to examine the relationship between phoning while driving and driver demographics, driving experience and exposure and characteristics of users. Among all participants, the study demonstrated that those who reported the use of hands‐free devices tended to use the cell phone more often and for a longer duration of time. Further, male drivers tended to use the cell phone while driving more frequently and for longer duration compared with female drivers. In regards to pulling off the road while using the cell phone, the study found this practice to be more prevalent among females, older drivers and more educated drivers. The study has also revealed other findings that are important for characterizing the trend towards using the cell phone while driving in Jordan.First published online: 10 Feb 2011